Shrub encroachment alters plant trait response to nitrogen addition in a semi-arid grassland - Li, Dan; Liu, Yanshu; Yang, Xiaohui; Zhang, Xiao; Shi, Zhongjie (Frontiers in Plant Science, 2023)
Encroachment of shrubs over large regions of arid and semi-arid grassland can affect grassland traits and growth under a background of increasing nitrogen (N) deposition. However, the effects of N input rates on species traits and the growth of shrubs on grasslands remain unclear. We examined the effects of six different N addition rates on the traits of Leymus chinensis in an Inner Mongolia grassland encroached by the leguminous shrub, Caragana microphylla. We randomly selected 20 healthy L. chinensis tillers within shrubs and 20 tillers between shrubs in each plot, measuring the plant height, number of leaves, leaf area, leaf N concentration per unit mass (LNCmass), and aboveground biomass. Our results showed that N addition significantly enhanced the LNCmass of L. chinensis. The aboveground biomass, heights, LNCmass, leaf area, and leaf number of plants within the shrubs were higher than those between shrubs. For L. chinensis growing between shrubs, the LNCmass and leaf area increased with N addition rates, leaf number and plant height had binomial linear relationships to N addition rates. However, the number of leaves, leaf areas and heights of plants within shrubs did not vary under various N addition rates. Structural Equation Modelling revealed N addition had an indirect effect on the leaf dry mass through the accumulation of LNCmass. These results indicate that the response of dominant species to N addition could be regulated by shrub encroachment and provide new insights into management of shrub encroached grassland in the context of N deposition.